Developmental differences in the perception of naturalistic human movements - Ntoumanis, Ioannis; Shestakova, Anna; Koriakina, Maria; Kadieva, Dzerassa; Kopytin, Grigory; Jääskeläinen, Iiro P. (Frontiers in Human Neuroscience, 2023)
It is widely believed that we are more attentive towards moving versus static stimuli. However, the neural correlates underlying the perception of human movements have not been extensively investigated in ecologically valid settings, nor has the developmental aspect of this phenomenon. Here, we set forth to investigate how human limb movements displayed in naturalistic videos influence the attentional engagement of children and young adults. Thirty-nine healthy participants (4-26 years old) were presented with naturalistic videos featuring human goal-directed movements, while neural activity was recorded using electroencephalography (EEG). Video scenes were automatically annotated as containing arm, leg or no movement, using a machine learning algorithm. The viewers’ attentional engagement was quantified by the intersubject correlation of EEG responses evoked by the videos. Our results demonstrate that scenes featuring limb movements, especially simultaneous arm and leg movements, elicit higher attentional engagement than scenes with no limb movement. Interestingly, this effect was found to diminish with age. Overall, our findings extend previous work on the perception of human motion by implementing naturalistic stimuli in the experimental design and extend the list of factors influencing the viewer’s engagement exerted by naturalistic videos.